2014
DOI: 10.1186/s12933-014-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of endothelial dysfunction in relation to impaired carbohydrate metabolism following pregnancy with gestational diabetes mellitus

Abstract: BackgroundHistory of gestational diabetes mellitus (GDM) identifies a very young population of females predisposed for type 2 diabetes and cardiovascular disease. Endothelial dysfunction might represent a shared precursor of both disorders. Hence, this study aimed to characterize endothelial biomarkers in relation to impaired insulin sensitivity and progression to overt diabetes early after index pregnancy.Methods108 women with previous GDM and 40 controls were included three to six months after delivery and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
0
30
1
1
Order By: Relevance
“…A great focus was placed on the production of IL-1β by placental cells in this study. It is primarily involved in the signaling cascade that triggers translocation of the transcription factor nuclear factor-kappa B (NFKB) into the nucleus where it induces the transcription of pro-and anti-inflammatory genes including IL-6, iNOS, and COX-2 [25]. Changes in IL-1β levels associated with the inflammatory biomarkers iNOS and MCP-1, as we found, suggest that lower mean blood glucose activates the expression of the inflammatory cascade at both plasma and placenta levels.…”
Section: Discussionmentioning
confidence: 99%
“…A great focus was placed on the production of IL-1β by placental cells in this study. It is primarily involved in the signaling cascade that triggers translocation of the transcription factor nuclear factor-kappa B (NFKB) into the nucleus where it induces the transcription of pro-and anti-inflammatory genes including IL-6, iNOS, and COX-2 [25]. Changes in IL-1β levels associated with the inflammatory biomarkers iNOS and MCP-1, as we found, suggest that lower mean blood glucose activates the expression of the inflammatory cascade at both plasma and placenta levels.…”
Section: Discussionmentioning
confidence: 99%
“…And Bo et al [ 28 ] showed women with previous GDM have been shown to express early markers of vascular dysfunction such as increased intima-media thickness of carotid arteries(C-IMT). Zajdenverg et al [ 29 ] showed microcirculation abnormality, evaluated by papillae rectification, was carried in young non-diabetic women with pGDM. Our study showed the normoglycemic women with pGDM were presented with elevated glycemic variability parameters, when compared with the women without pGDM.…”
Section: Discussionmentioning
confidence: 99%
“…Our presented study demonstrated that glycemic variability parameters SDBG, MBG, MODD, MAGE and AUC pp in pGDM group were higher than in the control group. Women with pGDM carried with early markers of vascular dysfunction [ 28 , 29 ]. Hence, it implies that glycemic variability may be related to early markers of vascular dysfunction in women with pGDM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, abnormal uterine blood flow has not been evidenced to affect glucose transfer to the fetus (Palacín et al 1985). Instead, endothelial dysfunction during GDM pregnancy may be associated with impaired cardiometabolism postpartum (Göbl et al 2014). The GDM placenta exhibits significant increases in key markers of endothelial dysfunction, such as endothelial-derived reactive oxygen and nitrative-derived species (Casanello et al 2007, Westermeier et al 2009.…”
Section: Endothelial Cell Dysfunctionmentioning
confidence: 99%